Old problems, new perspectives: nutritional and behavioral strategies to improve dairy cattle health - Fujan, Holly Elizabeth (Kansas State University, 2020)
The transition period, defined as 3 weeks prepartum to 3 weeks postpartum, is a high-risk time for disease in dairy cattle. There are many strategies to help prevent the onset of disease around calving. Of these, the use of a prepartum diet with a negative dietary cation anion difference (DCAD) is widely practiced to increase mobilization of calcium (Ca) from bone and reduce the incidence of hypocalcemia. However, the amount of Ca to supplement with a negative DCAD diet to promote optimal health during transition has remained in question. Additionally, technological advancements used to measure feeding behaviors in early lactation have evolved and could be valuable in predicting dry matter intake (DMI), lactation outcomes, and herd survival. This is important as greater DMI is associated with lower disease incidence during the transition period, leading to improved performance and reduced culling. An experiment using twenty-one pregnant, nonlactating cows completing at least one lactation was carried out to evaluate the effects of varying levels of Ca carbonate on DMI and metabolic acid-base status in a replicated 3 × 3 Latin square design utilizing 3 treatments and 3 periods. The only effect of treatment in this study was on urine pH, which increased linearly with increasing dietary Ca. However, greater DMI in Period 3 versus Period 1 in this study resulted in a greater degree of acidification during this time, as indicated by a lesser urinary pH. Greater Ca carbonate supplementation with no significant difference in Ca excretion suggests carbonate, not Ca, may be absorbed and converted to HCO₃⁻, with the excess HCO₃⁻ being excreted in urine. Therefore, when feeding high levels of Ca carbonate, urine pH may not accurately reflect acid-base status. In a second experiment, the relationships among feeding behavior variables collected during the first 21 d of lactation from 5 studies at Kansas State University were evaluated. Independent variables included meal frequency, meal length, meal size, and feeding time, along with parity, calving date, PTA for milk (PTAM) and 305-d mature equivalent milk (305MEM). Milk PTA, the slope of meal frequency, and mean meal length, specifically meal length during week 2, were predictive of 305MEM, and all were positively associated with 305MEM. For DMI, the quadratic function of feeding time, the intercept of meal frequency, parity and PTAM were predictive of DMI, with the quadratic function of week 2 feeding time and the intercept of meal frequency for week 2 significant when evaluating weekly feeding behaviors. The risk of being removed from the herd was increased by 13% for an additional meal/day in the first 21 d of lactation. Overall, strategies to improve herd health can be implemented both prepartum and postpartum to reduce disease and improve performance during the transition to lactation.
Keywords: Anionic; Calcium carbonate; Transition period; Biomonitoring; Forecasting; Dietary cation anion difference